Protodepalladation as a Strategic Elementary Step in Catalysis - O’Duill, Miriam L.; Engle, Keary M. (Synthesis, 2018)
Protodepalladation is the redox-neutral conversion of a C–Pd(II) bond into a C–H bond via reaction with a Brønsted acid. It is the microscopic reverse of Pd(II)-mediated C–H cleavage. In the context of catalytic reaction development, protodepalladation offers a means of converting organopalladium(II) intermediates into organic products without a change in oxidation state at the metal center. Hence, when integrated into catalytic cycles, it can be a uniquely enabling elementary step. The goal of this review is to provide an overview of protodepalladation, including exploration of different reaction types, discussion of literature examples, and analysis of mechanistic features. Our hope is that this review will stimulate other researchers in the field to pursue new applications of this underexploited step in catalysis.1 Introduction2 Mechanistic Considerations3 Examples of Synthetically Enabling Protodepalladation Reactions3.1 Alkenylpalladium Species3.2 Arylpalladium Species3.3 Palladium Enolates3.4 Alkylpalladium Species4 Conclusion
Keywords: palladium; palladacycles; alkenes; alkynes; cyclization; transition metals; protonation; metalation